ANALISA PEMELIHARAAN PREVENTIF ELECTROSURGICAL UNIT DI RUMAH SAKIT KOTA SUBULUSSALAM - Assauqi, Marzali Achmad; Primasyukra, Mhd. Aldi; Ulina, Sri; Pardosi, Putra Jaya (JURNAL MUTIARA ELEKTROMEDIK, 2024)
Electrosurgical Unit is a medical surgical device that utilizes high-frequency electric currents to cut, thicken and dry tissue during the operation process so that patients do not experience a lot of blood loss. 36 of 2009 concerning health states that the availability of medical devices must be safe, of good quality, and the public can be protected from harm caused by the use of medical devices that do not meet quality requirements. In Law No. 44 of 2009 concerning Hospitals, maintenance of equipment must be documented and evaluated periodically and continuously, so to carry out the mandate of the law, preventive maintenance must be carried out. The type of research used is descriptive qualitative research, which aims to analyze the maintenance of the Electrosurgical Unit by observing secondary maintenance data consisting of maintenance cards, SOPs, work tools etc. while observing primary data in the form of questionnaires so that the condition of preventive maintenance of ESU tools can be identified. already running. Based on the observations and analyzes that have been carried out, it is known that the preventive maintenance activities for the Electrosurgery Unit have been going well, such as technicians who have received training, maintenance funds are available, there are operating SOPs and calibration has also been carried out, but there are a number of things that must be improved, such as completing maintenance cards , Maintenance SOPs, performance tests, checking foot switches etc. periodically so that the condition of the ESU equipment can be monitored and documented on an ongoing basis.